Basic investigation on acoustic velocity change imaging method for quantitative assessment of fat content in human liver. (23rd June 2016) - Mano, Kazune; Tanigawa, Shohei; Hori, Makoto; Yokota, Daiki; Wada, Kenji; Matsunaka, Toshiyuki; Morikawa, Hiroyasu; Horinaka, Hiromichi
Abstract: Fatty liver is a disease caused by the excess accumulation of fat in the human liver. The early diagnosis of fatty liver is very important, because fatty liver is the major marker linked to metabolic syndrome. We already proposed the ultrasonic velocity change imaging method to diagnose fatty liver by using the fact that the temperature dependence of ultrasonic velocity is different in water and in fat. For the diagonosis of a fatty liver stage, we attempted a feasibility study of the quantitative assessment of the fat content in the human liver using our ultrasonic velocity change imaging method. Experimental results showed that the fat content in the tissue mimic phantom containing lard was determined by its ultrasonic velocity change in the flat temperature region formed by a circular warming ultrasonic transducer with an acoustic lens having an appropriate focal length. By considering the results of our simulation using a thermal diffusion equation, we determined whether this method could be applied to fatty liver assessment under the condition that the tissue had the thermal relaxation effect caused by blood flow.